(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Sakhnovskyy A. Y. Specialized education: ukrainian’s school education in searching of a new model. The author of the article covers urgent issues of provision of the specialized education in the modern school. Priority directions of its organization in transforming of the traditional educational environment are disclosed. It is noted that specialized education is a structural change which affects a range of important components of school life and has own place in its educational multi-level system by stimulating certain positive developments in education.